hsTropI: an early biomarker of acute coronary syndrome & MI - Sengupta Neogi, Sohini; Kumar Kapoor, Raj (International Journal of Medical Research and Review, 2017)
In the Emergency Department cardiac troponins are the preferred biomarkers for the diagnosis of acute myocardial infarction (MI) and are useful for risk stratification of patients with acute coronary syndrome (ACS) and stable ischemic heart disease. The introduction of ‘high sensitivity’ Troponins (hscTn) in many tertiary care centers has transformed the diagnostic scenario, wherein, the time from onset of chest pain to its diagnosis has significantly been reduced. With the advent of new hsTnI assays, which have a low limit of detection, low imprecision and low reference limits, the possibility of more patients with unstable angina being classified as having non-ST-elevation myocardial infarction (NSTEMI) will now increase. Its use will identify more high-risk patients with undifferentiated chest pain, that will help ‘rule-in’ or ‘rule-out’ acute myocardial infarction. In conclusion, it may be said that hsTropI is a sensitive, albeit less specific marker of MI. In patients of mildly elevated hsTropI and without evidence of ST elevation, a serial assessment of the biomarker is suggested. This will likely translate into more improved outcomes in this difficult patient population when ECG findings and clinical presentation do not suggest a clear diagnosis.